IMPLEMENTASI LOAD BALANCING BERBASIS CLOUD COMPUTING UNTUK MENDUKUNG INFRASTRUCTURE AS A SERVICE MENGGUNAKAN METODE QUICK SORT - Wintolo, Hero; Yusuf, Lalu Suwandi (Compiler, 2018)
Implementation of load balancing in cloud computing applications using quick sort method is a study to determine the access speed of each server. Design a cloud computing application using 4 laptops as application users and 3 laptops or PCs as servers in data storage. In sending data performed by the user application, the data will be distributed to the server that has been selected by the system with a quick sort method that sort the rest of the server capacity and then choose the server with the largest capacity. The stored data is placed in the htdocs file on the server. Based on the tests performed, cloud computing applications can run on at least 2 laptops using the windows version. Testing the server is also done by directly using the command prompt. During testing each server receives ping from the application to determine server performance in using load balancing. Testing without load balancing that sends data 50 times of 10 Mb to one server yields speed 15 ms, with 2 server divided by two in its data delivery that is as much as 25 times 10 Mb then speed 12 ms.